The Future of Genetically Modified Crops Lessons from the Green Revolution - Wu, Felicia (RAND Corporation, 2004)
The world is now on the cusp of a new agricultural revolution, the so-called Gene Revolution, in which genetically modified (GM) crops are tailored to address chronic agricultural problems in certain regions of the world. This monograph report investigates the circumstances and processes that can induce and sustain this new agricultural revolution. The authors compare the Green Revolution of the 20th century with the GM crop movement to assess the agricultural, technological, sociological, and political differences between the two movements.